Exploring the associations between elevated plasma SP-D levels and OSCAR gene expression as potential biomarkers in patients with COPD: a cross-sectional study - Saima Mukhtar; Saima Mukhtar; Nakhshab Choudhry; Saqib Saeed; Asif Hanif; Aamir J. Gondal; Nighat Yasmin (Frontiers Media S.A., 2024)
Background: Chronic obstructive pulmonary disease (COPD) imposes a substantial burden on patients and healthcare systems. Spirometry is the most widely used test to diagnose the disease; however, a surrogate marker is required to predict the disease pattern and progression.Objectives: The aim of the current study was to explore the association of elevated levels of plasma surfactant protein D (SP-D) with gene expression of osteoclast-associated receptor (OSCAR) and lung functions as potential diagnostic biomarkers of COPD.Methods: This cross-sectional study employed convenience sampling. As men compose the majority of patients in the outpatient department and with smoking being common among Pakistani men, choosing men offered a representative sample. Using a post-bronchodilator forced expiratory volume in the first second (FEV1) to a forced vital capacity (FVC) of less than 0.70 (FEV1/FVC <0.7), COPD patients were diagnosed on spirometry (n = 41). Controls were healthy individuals with FEV1/FVC >0.7 (n = 41). Plasma SP-D levels were measured using an enzyme-linked immunosorbent assay (ELISA). The gene expression of OSCAR was determined by real-time polymerase chain reaction (qPCR) and subsequently analyzed by the threshold cycle (Ct) method. Statistical Package for Social Sciences (SPSS) version 20 was used for statistical analysis.Results: The mean BMI of controls (25.66 ± 4.17 kg/m2) was higher than that of cases (23.49 ± 2.94 kg/m2 (p = .008)). The median age of controls was 49 years (interquartile range (IQR) 42.0-65.0 years) and that of cases was 65 years (IQR = 57.50-68.50). SP-D concentration was not significantly higher in COPD patients [4.96 ng/mL (IQR 3.26-7.96)] as compared to controls [3.64 ng/mL (IQR 2.60-8.59)] (p = .209). The forced expiratory ratio (FEV1/FVC) and FEV1 were related to gene expression of OSCAR (p = <.001). The gene expression of OSCAR was significantly related to SP-D (p = .034). A multiple regression model found FEV1 and FVC to have a significant effect on the gene expression of OSCAR (p-values <0.001 and 0.001, respectively).Conclusion: Gene expression of OSCAR was increased in COPD patients and related directly to SP-D levels and inversely to lung functions in cohort of this study, suggesting that OSCAR along with SP-D may serve as a diagnostic biomarker of COPD.